Peptide-Based Identification of Phytophthora Isolates and Phytophthora Detection in Planta - Berka, Miroslav; Greplová, Marie; Saiz-Fernández, Iñigo; Novák, Jan; Luklová, Markéta; Zelená, Pavla; Tomšovský, Michal; Brzobohatý, Břetislav; Černý, Martin (International journal of molecular sciences, 2020)
Phytophthora is arguably one of the most damaging genera of plant pathogens. This pathogen is well suited to transmission via the international plant trade, and globalization has been promoting its spread since the 19th century. Early detection is essential for reducing its economic and ecological impact. Here, a shotgun proteomics approach was utilized for Phytophthora analysis. The collection of 37 Phytophthora isolates representing 12 different species was screened for species-specific peptide patterns. Next, Phytophthora proteins were detected in planta, employing model plants Solanum tuberosum and Hordeum vulgare. Although the evolutionarily conserved sequences represented more than 10% of the host proteome and limited the pathogen detection, the comparison between qPCR and protein data highlighted more than 300 protein markers, which correlated positively with the amount of P. infestans DNA. Finally, the analysis of P. palmivora response in barley revealed significant alterations in plant metabolism. These changes included enzymes of cell wall metabolism, ROS production, and proteins involved in trafficking. The observed root-specific attenuation in stress-response mechanisms, including the biosynthesis of jasmonates, ethylene and polyamines, and an accumulation of serotonin, provided the first insight into molecular mechanisms behind this particular biotic interaction.
Keywords: listy rostlin; Phytophthora infestans; P. infestans; Chromatography, Liquid; polymerázová řetězová reakce; Phytophthora; reaktivní formy kyslíku; Hordeum vulgare; Hordeum; proteom; proteomics; Mass Spectrometry; rostlinné proteiny; Plant Proteins; chromatografie kapalinová; nemoci rostlin; Stress, Physiological; proteomika; Reactive Oxygen Species; leaf inoculation; ječmen (rod); metabolické sítě a dráhy; Plant Leaves; Peptides; peptidy; Plant Diseases; Polymerase Chain Reaction; hmotnostní spektrometrie; Proteomics; fyziologický stres; Proteome; P. palmivora; Metabolic Networks and Pathways; Solanum tuberosum